Comparing graphs and text: Effects of complexity and task - Sunjung Kim; Linda J. Lombardino (Bern Open Publishing, 2015)
Graphs are commonly believed to facilitate users' compre-hension. We explored the effect of graphs on comprehension compared to text, manipulating content complexity (single bar vs. double bar graphs) and question type (point-locating vs. comparison questions). A total 78 college students viewed graph and text stimuli and answered comprehension questions while their eye movements were recorded. The results indicate that students do not always process graphs more efficiently than text conveying the same information. Students processed graphs significantly faster than text only when the more complex questions were shown. When the more complex graphic patterns were presented, the advantage of graphs over text became less apparent. The students also spent the majority of their time looking at specific information on the axes and label regions of the graphs with the increasing complexity of graphs and tasks. These findings are discussed related to theories of learning including cognitive load theory and perceptual salience theory.